Expressão imuno-histoquímica das integrinas a2ß1, a3ß1 e a5ß1 em adenoma pleomórfico de glândula salivar menor e maior e carcinoma adenóide cístico - Miguel, Márcia Cristina da Costa (2005)
Pleomorphic adenoma and adenoid cystic carcinoma (ACC) consist benign and malignant neoplasm from salivary gland, respectively. These neoplasms share some characteristics, such as cellular origin and considerable production of extracellular matrix, however, with distinct biological behavior. The aim of the present study was to compare the expression of D2E1, D3E1 e D5E1 integrins in pleomorphic adenoma from minor and major salivary glands and ACCs. Furthermore, it was investigated possible differences in the expression of these integrins according to histological subtypes of ACC. Fourteen cases of pleomorphic adenoma from major salivary gland, fourteen cases from minor salivary gland and ten cases of ACC were selected. It was taken into consideration the presence or absence, localization and intensity of integrin immunoexpression. The cases of pleomorphic adenoma were grouped in order to compare the expression between the distinct neoplasms. It was observed a highly significant difference (p<0,0001) in relation to D2E1 integrin between the neoplasms since pleomorphic adenoma showed a pronounced immunostaining. It was not possible to perform statistical tests considering the D2E1 integrin expression; nevertheless, it could be observed a tendency of higher staining in pleomorphic adenoma. For comparative reasons the cases ACCs were divided in two groups: solid and tubular/cribriform. It was not detected significant differences in regard to D2E1 integrin; and statistical analysis could not be realized in relation to D3E1 and D5E integrin expression. However, it was also verified a tendency of absence or reduced expression in the solid subtype. It can be concluded that the reduced D2E1 integrin expression observed in CACs may be related to a lesser degree of cell differentiation in this neoplasm and the reduced D5E1 integrin expression can be associated with aggressive biological behavior. Moreover, the absence and/or reduced expression of the studied integrins in solid ACC suggests a role in pathogenesis and more aggressive biological behavior of this histological subtype